2000
DOI: 10.1103/physrevlett.85.54
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Backward-Directed Multiphoton-Excited Fluorescence from Dielectric Microcavities

Abstract: We demonstrate theoretically and experimentally that one-, two-, and three-photon excited fluorescence from dye molecules in spherical microcavities has an asymmetrical angular distribution and is enhanced in the backward direction. The enhancement ratios (of intensities at 180 degrees and 90 degrees ) are 9, 5, and 1.8 for three-, two-, and one-photon excitation, respectively. Even larger ratios are expected for microspheres with an index of refraction larger than that used in the experiments. Because of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 16 publications
3
43
0
Order By: Relevance
“…A significant improvement of our set-up in terms of sensitivity would be the excitation of the particles through the same objective as for the fluorescence collection, like in epi-microscopy. MPEF from individual aerosol particles is indeed strongly enhanced in the backward direction [22,23] (up to a factor 10 for 3PEF). The important anti-Stokes shift between the 790 nm excitation and MPEF would allow efficient rejection at the dichroic beamsplitter.…”
Section: Resultsmentioning
confidence: 86%
“…A significant improvement of our set-up in terms of sensitivity would be the excitation of the particles through the same objective as for the fluorescence collection, like in epi-microscopy. MPEF from individual aerosol particles is indeed strongly enhanced in the backward direction [22,23] (up to a factor 10 for 3PEF). The important anti-Stokes shift between the 790 nm excitation and MPEF would allow efficient rejection at the dichroic beamsplitter.…”
Section: Resultsmentioning
confidence: 86%
“…33,34 This unexpected behavior is extremely attractive for remote detection schemes, such as Lidar applications. Localization is achieved by the non-linear processes themselves, which typically involve the nth power of the internal intensity I n (r) (r for position inside the particle).…”
Section: Multi-photon Excited Fluorescence (Mpef) and Ppd In Aerosol mentioning
confidence: 99%
“…The depletion factor d reaches 80% for Trp droplets and 60% for FMN droplets (to be compared to 50% and 15% in liquids, respectively). Some tentative explanations could be invoked for this unexpectedly high efficiency, but the definitive reason is not clear yet: (1) The spatial overlap between pump and probe pulses might be enhanced by the shape of the droplet; (2) the spherical shape induces hot spots inside the droplet where intensities are up to 100 times higher than the incident one, 33,34 but the total hot spot volume is rather small; (3) there might be some surface effects (orientation of molecules on the surface) that would enhance the two photon absorption.…”
Section: Multi-photon Excited Fluorescence (Mpef) and Ppd In Aerosol mentioning
confidence: 99%
See 1 more Smart Citation
“…We indeed demonstrated that light emission from airborne particles is enhanced in the backward direction, especially if the process is nonlinear. [21][22][23] Flexibility on the type of bacteria is provided by seeding the thermodenuder with two piezo-nozzles, one dedicated to the spread of the bacteria A (e.g. Gram+) and the other to bacteria B (e.g.…”
Section: Application To Bacteria Detectionmentioning
confidence: 99%